Integrasi Teknologi AI dalam Pembelajaran STEM di Sekolah Menengah : Perspektif Personalisasi, Tantangan, dan Implikasi - Uban Subandi; Supardi US (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Artificial Intelligence in STEM education has gained attention because it has the potential to transform the learning and teaching process. The study aims to systematically analyze the application of AI technology in STEM education, focusing on the impact on student engagement, learning outcomes, and teaching methods. The study used the Systematic Literature Review (SLR) method with PRISMA guidance, Articles published in the last ten years, to ensure the selection process on the latest trends. The main findings show that AI-based tools, such as adaptive learning systems, intelligent tutoring systems, and automated assessment platforms, significantly enhance the personalized learning experience and encourage students' critical thinking skills in STEM learning. Challenges such as ethical considerations, data privacy issues, and the digital divide are still issues that need attention. Overall, the study shows that AI has a crucial role in STEM education in the future and recommends a strategic framework to overcome the challenges of AI implementation. The main findings of the article provide a basis for educators, policymakers, and researchers to develop and implement AI-based innovations effectively in STEM education.